Penerapan Algoritma Booyer Moore Pada Aplikasi Teka Teki Silang (TTS) - Ramadhan, M. Ibnu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Crossword or abbreviated with TTS is a game to fill the empty spaces (in the form of white boxes) with letters that form a word based on the instructions given. In further developments, this puzzle is also intended for problems that must be filled with numbers. To fill in the letters in each box, instructions are given that are divided into